MECP2 mutations affect ciliogenesis: a novel perspective for Rett syndrome and related disorders. Issue 6 (8th May 2020) - Frasca, Angelisa; Spiombi, Eleonora; Palmieri, Michela; Albizzati, Elena; Valente, Maria Maddalena; Bergo, Anna; Leva, Barbara; Kilstrup‐Nielsen, Charlotte; Bianchi, Federico; Di Carlo, Valerio; Di Cunto, Ferdinando; Landsberger, Nicoletta
Abstract: Mutations in MECP2 cause several neurological disorders of which Rett syndrome (RTT) represents the best‐defined condition. Although mainly working as a transcriptional repressor, MeCP2 is a multifunctional protein revealing several activities, the involvement of which in RTT remains obscure. Besides being mainly localized in the nucleus, MeCP2 associates with the centrosome, an organelle from which primary cilia originate. Primary cilia function as "sensory antennae" protruding from most cells, and a link between primary cilia and mental illness has recently been reported. We herein demonstrate that MeCP2 deficiency affects ciliogenesis in cultured cells, including neurons and RTT fibroblasts, and in the mouse brain. Consequently, the cilium‐related Sonic Hedgehog pathway, which is essential for brain development and functioning, is impaired. Microtubule instability participates in these phenotypes that can be rescued by HDAC6 inhibition together with the recovery of RTT‐related neuronal defects. Our data indicate defects of primary cilium as a novel pathogenic mechanism that by contributing to the clinical features of RTT might impact on proper cerebellum/brain development and functioning, thus providing a novel therapeutic target. Synopsis: MeCP2 mutations affect homeostasis and functioning of the primary cilium, a "sensory antenna" whose defects are often linked with mental illness. Restoration of ciliogenesis promotes Mecp2 null neuronal maturation, suggesting new therapeutic approaches for Rett syndrome. MeCP2 deficiency affects ciliogenesis in cultured cells and in the mouse brain. The cilium‐related Sonic Hedgehog pathway, which is essential for brain development and functioning, is defective in cells modeling Rett syndrome. In Rett cells, the increased HDAC6 activity causes microtubule instability, therefore affecting ciliogenesis. HDAC6 inhibition at the primary cilium level ameliorates dendritic arborization and synaptogenesis in Mecp2 null neurons, therefore prompting future preclinical studies. Abstract : MeCP2 mutations affect homeostasis and functioning of the primary cilium, a "sensory antenna" whose defects are often linked with mental illness. Restoration of ciliogenesis promotes Mecp2 null neuronal maturation, suggesting new therapeutic approaches for Rett syndrome.